The Effect of Information Security Systems on Service Quality in E-Commerce Systems - Surya Wijaya, Abi; Elya Rohimi, Upit; Asyifah, Alifiatun (Riviera Publishing, 2023)
The current development of information technology has brought significant changes in the business world, including the e-commerce system. However, this technological development also brings new risks, namely the threats to information security in e-commerce systems. Therefore, e-commerce companies must develop an effective information security system to minimize security risks and improve service quality. This study aims to analyze the effect of information security systems on service quality in e-commerce systems. The method used in this research is qualitative by conducting interviews with several e-commerce system users and management of e-commerce companies related to information security systems. The results show that an effective information security system significantly influences the quality of service in e-commerce systems. E-commerce system users have more confidence in systems with robust information security systems, improve data integrity, and reduce the possibility of problems or failures in e-commerce systems. In addition, management who is actively involved in paying attention to information security systems will show concern for the security of user data and increase user trust in the e-commerce system being operated. e-commerce companies must prioritize developing and continuously improving their information security systems and ensure management involvement in maintaining data security to gain user trust and loyalty. This, in turn, can enhance the service quality provided and positively impact future business growth.